KARAKTERISTIK DAN PENGETAHUAN WANITA USIA SUBUR (WUS) DENGAN MINAT MELAKUKAN DETEKSI DINI KANKER SERVIKS MELALUI METODE INSPEKSI VISUAL ASAM ASETAT (IVA) DI PUSKESMAS NUMBING - Apriani, Finta; Suryanti, Suryanti (Universitas Batam, 2021)
Cervical cancer is the second cancer which causes death of women in the world. Governmenth a simple mented an early detection program using visual inspection of acetic acid, but this has not been implemented properly because level of awareness of Indonesian women about danger sofcervical cancer and for early detection of cervical cancer is still low. The objective of this study is to determine the characteristics and knowledge of eligible woman on aninterest to early detection of cervical cancer using Visual Inspection with Acetic Acid) method. This research was included into analytical survey design with crosssectional approach. Population of this study wast eligible women who visited to Numbing Public Health Center. Sample taken was around 48 women. This research was conducted on December to February 2021. The instrument used for collecting data was questionnaire. Data was analyzed by using Chi Square statistical test. Result of 48 respondents showed that mostly, they had low education level about 35 respondents (72,9%). Dealing with the employment status, 29 respondents (60,4%) had jobs. More than half of respondents had low economic status around 27 respondents (56,3%). Inconclusion, there is a significant correlation of education with p=0,000, employment status with p=0,002, Economic status with p=0,003, knowledge with p=0,003 on an interest to early detection of cervical cancer using Visual Inspection with Acetic Acid (VIA) method. The suggestion for respondents is hopefully they will have an interest to detect early the cervical cancer using Visual Inspection with Acetic Acid method.